Eats roots and leaves. Can edible horticultural crops address dietary calcium, magnesium and potassium deficiencies? - Broadley, Martin R.; White, Philip J. (Proceedings of the Nutrition Society, 2010)
Human individuals require at least 20 inorganic elements (‘minerals’) for normal functioning. However, much of the world's population is probably deficient in one or more essential minerals and at increased risk of physiological disorders. Addressing these ‘hidden hungers’ is a challenge for the nutrition and agriculture sectors. Mineral deficiencies among populations are typically identified from dietary surveys because (1) minerals are acquired primarily from dietary sources and (2) (bio)assays of mineral status can be unreliable. While dietary surveys are likely to under-report energy intakes, surveys show that 9% of all UK and US adults consume Ca and Mg, and 14% of adults consume K, at quantities below the UK lower reference nutrient intake, and are therefore at risk of deficiency. Low dietary Ca, Mg and K intakes can be caused by energy-malnourishment and by cultural and economic factors driving dietary conservatism. For example, cereal grains routinely displace vegetables and fruits in the diet. Cereal grains have low concentrations of several minerals, notably Ca, as a consequence of their physiology. Low grain mineral concentrations are compounded when cereal crops are grown in soils of low mineral phytoavailability and when grain is processed. In this paper, the impact of increased vegetable consumption and horticultural biofortification, i.e. enhancing crop mineral content through breeding and agronomy, on intakes of the major minerals Ca, Mg and K is assessed. Despite low energy intake from horticultural crops generally, increased vegetable consumption and biofortification would significantly improve dietary intakes of Ca, Mg and K.